UJI VALIDITAS DAN RELIABILITAS KUESIONER PDQ39 VERSI BAHASA INDONESIA PADA PASIEN PARKINSON - Oktariza, Yasinda; Amalia, Lia; Sobaryati, Sobaryati; Kurniawati, Media Y (Acta Pharmaceutica Indonesia, 2025)
The PDQ-39 questionnaire is a disease-specific instrument used to measure the health-related quality of life (HRQoL) in Parkinson's disease patients. HRQoL assessment is one of key parameter for evaluating patient outcomes after receiving pharmacological and non-pharmacological treatments. The PDQ-39 questionnaire has been widely used in various countries, including Indonesia. However, no studies about validating and assessing the reliability of the Indonesian version of the PDQ-39 questionnaire have been published. This study aims to evaluate the validity and reliability of the Indonesian version of the PDQ-39 questionnaire. A cross-sectional study was conducted using a consecutive sampling technique. The study began with a language adaptation process. Questionnaire validity was assessed using Pearson’s Product-Moment correlation, while reliability was tested using Cronbach’s Alpha coefficient (>0.6). The questionnaire was administered to 31 outpatients at the Neurology Clinic of RSUD Arifin Achmad, Riau Province, and RSAU Dr. M. Salamun Bandung. Validity testing demonstrated that most correlation coefficients (r) between domains were acceptable (0.470–0.892) and statistically significant at p<0.01, except for item number twenty (r=0.345). Reliability testing showed a high overall Cronbach’s Alpha value of 0.924. Based on these findings, the Indonesian version of the PDQ-39 questionnaire is a valid and reliable instrument for measuring the quality of life in Parkinson's disease patients.